Penerapan Discovery Learning dalam Mewujudkan Pembelajaran Efektif - Saidan Lubis (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[THE APPLICATION OF DISCOVERY LEARNING IN OBTAINING EFFECTIVE LEARNING (STUDY OF TRAINING FOR ISLAMIC JURISPRUDENCE TEACHER OF VOCATIONAL SCHOOLS IN RELIGIOUS TRAINING CENTER OF PADANG)] This research aimed to analyze whether the application of the Discovery Learning model can realize effective learning in the training of Ushul Fikih MAK teacher at the Religious Training Center of Padang in 2019. The research method used was descriptive qualitative using a survey and interview of 30 trainees. The results show that the application of discovery learning models makes learning more effective because it adopts scientific steps in building knowledge and encourages trainees to have creative thinking skills to find problems, formulate hypotheses, collect data with various techniques, analyze, draw conclusions, and communicating what was found. This is under Ushul Fikih's mindset, which is to encourage and train trainees to investigate (al-iktisyaf) to find something themselves and in turn, produce knowledge that is truly meaningful. The application of discovery learning models in the training activities of the subjects of Usul Fikih MAK in 2019 at the Padang Education and Training Center turned out to be able to change the passive learning conditions to become effective, active and creative, changing learning from the teacher oriented / al-murtakiz 'style of al-mudarrib to student oriented / al-murtakiz 'ala al-musyarikin, and also change the mode of expositor trainees who always receive full information from widyaiswara into a discovery that is searching and finding information on their own